Effects of laughter yoga on patients receiving hemodialysis - Li, Ting; Soh, Kim Lam; Zakaria, Nor Fadhlina; Pang, Yuanyue; Wang, Pengpeng; Hu, Niaona (Wolters Kluwer Health, 2024)
When it comes to end-stage renal disease patients, hemodialysing is one of the most critical treatments they can receive. Even if they received hemodialysis (HD) treatment regularly, patients would experience many complications such as cardiovascular disease, fatigue, anxiety, depression, sleep disturbances, and a declining quality of life. Laughter Yoga has been reported to have many positive effects on patients with chronic illnesses. By removing or reducing stress, Laughter Yoga (LY) helps to improve patients’ quality of life, Thus, they have a longer chance of survival. However, the effect of Laughter Yoga on HD patients is generally inconclusive. Objective is to evaluate LY’s impact on HD patients. We searched electronic databases that included Web of Science, Embase, PubMed, the Cochrane Library, Wanfang, China National Knowledge Infrastructure, and clinical trial registries. The search period was from their inception to January 29, 2023. The search keywords included laughter therapy, laughter yoga, laugh, hemodialysis, dialysis, and renal dialysis. The systematic review included both randomized controlled trials (RCTs) and quasi-experiments studies. Three RCTs and three non-RCTs met the inclusion criteria. Laughter Yoga showed patients having improvement in several outcomes such as life quality, pain severity, sleep quality, subjective well-being, mood, depression, blood pressure, and vital capacity. A well-designed RCT will be developed to further test the potential benefits of LY for HD patients.